Agreement between coding schemas used to identify bleeding‐related hospitalizations in claims analyses of nonvalvular atrial fibrillation patients. Issue 1 (23rd January 2018) - Coleman, Craig I.; Vaitsiakhovich, Tatsiana; Nguyen, Elaine; Weeda, Erin R.; Sood, Nitesh A.; Bunz, Thomas J.; Schaefer, Bernhard; Meinecke, Anna‐Katharina; Eriksson, Daniel
Abstract : Background: Schemas to identify bleeding‐related hospitalizations in claims data differ in billing codes used and coding positions allowed. We assessed agreement across bleeding‐related hospitalization coding schemas for claims analyses of nonvalvular atrial fibrillation (NVAF) patients on oral anticoagulation (OAC). Hypothesis: We hypothesized that prior coding schemas used to identify bleeding‐related hospitalizations in claim database studies would provide varying levels of agreement in incidence rates. Methods: Within MarketScan data, we identified adults, newly started on OAC for NVAF from January 2012 to June 2015. Billing code schemas developed by Cunningham et al., the US Food and Drug Administration (FDA) Mini‐Sentinel program, and Yao et al. were used to identify bleeding‐related hospitalizations as a surrogate for major bleeding. Bleeds were subcategorized as intracranial hemorrhage (ICH), gastrointestinal (GI), or other. Schema agreement was assessed by comparing incidence, rates of events/100 person‐years (PYs), and Cohen's kappa statistic. Results: We identified 151 738 new‐users of OAC with NVAF (CHA2DS2‐VASc score = 3, [interquartile range = 2–4] and median HAS‐BLED score = 3 [interquartile range = 2–3]). The Cunningham, FDA Mini‐Sentinel, and Yao schemas identified any bleeding‐related hospitalizations in 1.87% (95% confidence interval [CI]: 1.81‐1.94), 2.65% (95% CI: 2.57‐2.74), and 4.66% (95% CI: 4.55‐4.76) of patients (corresponding rates = 3.45, 4.90, and 8.65 events/100 PYs). Kappa agreement across schemas was weak‐to‐moderate (κ = 0.47–0.66) for any bleeding hospitalization. Near‐perfect agreement (κ = 0.99) was observed with the FDA Mini‐Sentinel and Yao schemas for ICH‐related hospitalizations, but agreement was weak when comparing Cunningham to FDA Mini‐Sentinel or Yao (κ = 0.52–0.53). FDA Mini‐Sentinel and Yao agreement was moderate (κ = 0.62) for GI bleeding, but agreement was weak when comparing Cunningham to FDA Mini‐Sentinel or Yao (κ = 0.44–0.56). For other bleeds, agreement across schemas was minimal (κ = 0.14–0.38). Conclusions: We observed varying levels of agreement among 3 bleeding‐related hospitalizations schemas in NVAF patients.